Complete mitochondrial genome of the hybrid loach of Paramisgurnus dabryanus ssp. (female) and Misgurnus anguillicaudatus (male). Issue 1 (2nd January 2018) - Liang, Xia; Zhu, Daoyu; Li, Xiaodong; Cai, Kejun; Zhang, Haili; Zhang, Guosong
Abstract: The hybrid loach of P. dabryanus ssp. (female) and M. anguillicaudatus (male) has the desirable trait of growth performance. There is no report of the complete genome of this hybrid. In this study, the complete mitochondrial genome of this hybrid loach was obtained, and the genome is 16, 569 bp in length, including two ribosomal RNA genes. Thirteen proteins-coding genes, 22 transfer RNA genes, and a non-coding control region, the gene composition and order of which was similar to most reported from other vertebrates. Sequence analysis showed that the overall base composition is 29.5% for A, 27.5% for T, 26.4% for C, and 16.6% for G. The sequence is a slight A + T bias of 57.0%. The phylogenetic tree showed that the hybrid loach to be one of Paramisgurnus, and the relationships of M. anguillicaudatus were closer. Also the mitochondrial genome sequence of loach were aligned by BLAST, compared with Cobitinae the sequence similarity could reach >90%, and the similarity to Paramisgurnus was >99%. Mitogenome information from this study could be a useful basis for conservation and phylogenetics of this hybrid loach.